Optical molecular imaging‐guided radiation therapy part 1: Integrated x‐ray and bioluminescence tomography. Issue 9 (20th July 2017) - Shi, Junwei; Udayakumar, Thirupandiyur S.; Wang, Zhiqun; Dogan, Nesrin; Pollack, Alan; Yang, Yidong
Abstract : Purpose: X‐ray CT faces challenges in differentiating tumors from surrounding healthy tissues. A bioluminescence tomography (BLT) system which can directly reconstruct the internal luminescent tumors, was developed and integrated with CT system to accurately guide radiation dose delivery. Methods: The BLT system, employing a lens‐coupled CCD camera, was physically registered with an onboard cone beam CT system in an image‐guided small animal arc radiation treatment system (iSMAART). The onboard CT provides animal anatomy and accurate surface contour used to construct the three‐dimensional mesh for the BLT reconstruction. Bioluminescence projections were captured from multiple angles, once every 90° rotation. The BLT reconstruction was performed on an orthotopic prostate tumor model to evaluate its robustness and accuracy in locating and delineating bioluminescent tumors. The location and volume of the tumor identified from iodinated contrast CT was used to validate the BLT performance. Phantom experiment was also conducted to confirm the precision of BLT‐guided radiation. Results: The BLT was able to accurately locate the bioluminescent tumors with < 0.5 mm error. The tumor volume in BLT was significantly correlated with that in the iodinated contrast CT (R 2 = 0.81, P < 0.001). Phantom experiments further validated that BLT can be used to guide radiation with submillimeter accuracy. Conclusion: Together with CT, BLT can provide precision radiation guidance and robust tumor volume assessment in small animal cancer research.